¿PUEDEN CANCELARSE UNAS ELECCIONES? - Barrat Esteve, Jordi (Revista de Derecho, 2020)
The worldwide 2020 pandemic obliged public authorities to customize many procedures to a new reality and the elections were not an exception. The text analyzes how Spain managed to hold in July the Galician and Basque elections that were originally scheduled for April. In this regard, various questions arose, among which the decision itself to cancel elections, the chance to proceed during the state of emergency, who should adopt such a decision and, in a more operational way, what measures to adopt for voters who were in quarantine during the election day. There were a range of exceptional mechanisms in which a balance, always uncertain, had to be sought between the holding of elections and the respect for fundamental rights and the constitutional framework as a whole.